Pharmacy Practice and Education in Finland - Jouni Hirvonen; Outi Salminen; Katariina Vuorensola; Nina Katajavuori; Helena Huhtala; Jeffrey Atkinson (MDPI AG, 2019)
The Pharmacy Education in Europe (PHARMINE) project studies pharmacy practice and education in the European Union (EU) member states. The work was carried out using an electronic survey sent to chosen pharmacy representatives. The surveys of the individual member states are now being published as reference documents for students and staff interested in research on pharmacy education in the EU, and in mobility. This paper presents the results of the PHARMINE survey on pharmacy practice and education in Finland. Pharmacies have a monopoly on the dispensation of medicines. They can also provide diagnostic services. Proviisori act as pharmacy owners and managers. They follow a five-year (M.Sc. Pharm.) degree course with a six-month traineeship. Farmaseutti, who follow a three-year (B.Sc. Pharm.) degree course (also with a six-month traineeship), can dispense medicines and counsel patients in Finland. The B.Sc. and the first three years of the M.Sc. involve the same course. The current pharmacy curriculum (revised in 2014) is based on five strands: (1) pharmacy as a multidisciplinary science with numerous opportunities in the working life, (2) basics of pharmaceutical sciences, (3) patient and medication, (4) optional studies and selected study paths, and (5) drug development and use. The learning outcomes of the pharmacy graduates include (1) basics of natural sciences: chemistry, physics, technology, biosciences required for all the students (B.Sc. and M.Sc.), (2) medicine and medication: compounding of medicines, holism of medication, pharmacology and biopharmaceutics (side-effects and interactions), patient counseling, efficacy and safety of medicines and medication, (3) comprehensive and supportive interactions of the various disciplines of pharmacy education and research: the role and significance of pharmacy as a discipline in society, the necessary skills and knowledge in scientific thinking and pharmaceutical research, and (4) basics of economics and management, multidisciplinarity, hospital pharmacy, scientific writing skills, management skills. In addition, teaching and learning of “general skills„, such as the pharmacist’s professional identity and the role in society as a part of the healthcare system, critical and creative thinking, problem-solving skills, personal learning skills and life-long learning, attitude and sense of responsibility, and communication skills are developed in direct association with subject-specific courses. Professional specialization studies in industrial pharmacy, and community and hospital pharmacy are given at the post-graduate level at the University of Helsinki.